PERAN MEDIA SOSIAL DALAM MEMPROMOSIKAN KULINER NUSANTARA - Amanda Diva Vebiyan; Joan Andriona; Hani Rahmawati Johan; Gavriella Ceacilia Christie Ratu Edo; Miranda Bellany; Sri Tiatri (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT Indonesian cuisine not only reflects the diversity of flavors but is also an integral part of Indonesia's cultural identity, which continues to face challenges in the era of globalization. This article aims to examine the role of social media in promoting Indonesian cuisine through a literature review approach, analyzing various scientific publications from the past ten years. The research began with keyword identification, followed by literature search and selection, and finally, analysis of findings from relevant sources. The study results show that digital platforms such as Instagram, TikTok, and YouTube play a strategic role in increasing the visibility and attractiveness of local cuisine, especially among young people. Social media has been proven to contribute to the empowerment of MSMEs, enhance cultural literacy, and strengthen local identity. Besides being a promotional medium, social media also serves as a cultural advocacy tool that actively encourages community participation, especially among young people, in the preservation of traditional cuisine. Nevertheless, challenges such as content polarization, disinformation, and consistency of cultural narratives are issue that need to be anticipated. This study emphasizes the importance of authentic, visually-oriented content marketing strategies aligned with digital trends to sustainably strengthenthe presence of Indonesian cuisine. ABSTRAK Kuliner Nusantara tidak hanya mencerminkan keberagaman rasa, tetapi juga merupakan bagian integral dari identitas budaya Indonesia yang terus menghadapi tantangan di era globalisasi. Artikel ini bertujuan untuk menelaah peran media sosial dalam mempromosikan kuliner Nusantara melalui pendekatan tinjauan pustaka terhadap berbagai literatur ilmiah selama sepuluh tahun terakhir. Penelitian ini diawali dengan identifikasi kata kunci, dilanjutkan dengan pencarian dan seleksi literatur, hingga analisis temuan dari berbagai sumber yang relevan. Hasil kajian menunjukkan bahwa platform digital seperti Instagram, TikTok, dan YouTube memainkan peran strategis dalam meningkatkan visibilitas dan daya tarik kuliner lokal, terutama di kalangan generasi muda. Media sosial terbukti berkontribusi terhadap pemberdayaan UMKM, peningkatan literasi budaya, serta penguatan identitas lokal. Selain sebagai media promosi, media sosial juga berfungsi sebagai alat advokasi budaya yang mendorong partisipasi aktif masyarakat, khususnya generasi muda, dalam pelestarian kuliner tradisional. Meskipun demikian, tantangan seperti polarisasi konten, disinformasi, dan konsistensi narasi budaya menjadi isu yang perlu diantisipasi. Kajian ini menegaskan pentingnya strategi pemasaran berbasis konten autentik dan visual yang selaras dengan tren digital untuk memperkuat eksistensi kuliner Nusantara secara berkelanjutan.